The specialist of a specialist: the natural history of the predispersal seed predator weevil Hemicolpus abdominalis (Coleoptera: Curculionidae) - Sanz-Veiga, Priscila A. [UNESP]; Polizello, Diego S. [UNESP]; Silva, Daniel P.; Savaris, Marcoandre; Amorim, Felipe W. [UNESP] (Wiley, 2021)
1. The reproduction of specialised endophagous insects relies on a fine temporal synchronization between the insect and its host plant phenology. 2. Since the spatial distribution and local prevalence of specialised insects depend on both environmental conditions and biotic interactions, in this study, we assessed whether the life cycle of the predispersal seed feeding weevil, Hemicolpus abdominalis (Curculionidae), is synchronised with the reproductive phenology of its host plant, Tocoyena formosa (Rubiaceae) in the Brazilian Cerrado. Following an ecological niche modelling approach, we also tested whether the predicted distribution of this specialised weevil matches that of its host plant. 3. We observed a tight synchronization between the weevil reproduction and its host plant reproductive phenology. After emergence from the fruits, adult weevils enter in reproductive diapause, with reproductive development resuming in the next reproductive season, which indicates the univoltism of this species. 4. There was a high spatial congruence in the distribution of H. abdominalis and its host plant. Since the reproduction of H. abdominalis is synchronised with the host plant phenology, temporal mismatches between the weevil life cycle, and plant reproduction may affect the long-term population prevalence of the insect. 5. The life cycle of the predispersal seed feeding weevil, H. abdominalis, depends on a close match with the host plant reproductive phenology, whose fruit production is entirely dependent on long-tongued hawkmoth pollinators. Hence, we highlight the importance of both biotic and abiotic conditions in shaping the distribution range of a specialised endophagous insect.
Keywords: Cerrado; Conoderinae; fruits; host plant; life cycle; phenological synchrony; spatial distribution; Tocoyena formosa